Evaluating the Potential of Refuse Derived Fuel (RDF) in Cement Production: a Comparative Analysis of RDF Variations In Indonesia's Emplacement Pluit, Jakarta - Sari, Mega Mutiara; Inoue, Takanobu; Septiariva, Iva Yenis; Yokota, Kuriko; Notodarmodjo, Suprihanto Mediawan; Kato, Shigeru; Suhardono, Sapta Cahya; Al Ghifari, Rizal Muhammad; Suryawan, I Wayan Koko (Jurnal Bahan Alam Terbarukan, 2024)
This study critically evaluated the potential of Refuse Derived Fuel (RDF) as a sustainable substitute for coal in the cement manufacturing process. Using Emplacement Pluit's waste as a primary source, three distinct RDF variations were analyzed: RDF A (comprised purely of PET Charcoal), RDF B (a 50-50 combination of PET Charcoal and organic waste), and RDF C (solely organic waste). Among the parameters evaluated were moisture content, ash content, and calorific value. The results indicated RDF A's superior quality, with a moisture content of 2.6%, ash content of 0.7%, and a calorific value of 25.1 MJ/kg. In stark contrast, RDF C exhibited a high waste reduction potential at 80.5%, but its calorific value fell short of Korean standards. RDF B, balancing quality and reduction potential, achieved a 98.9% waste reduction and met Korean RDF standards, making it the most viable alternative to coal in cement production. The study underscores the significant potential of integrating RDF in industrial practices, particularly cement kilns. It offers insight into optimizing waste management strategies in line with the 'zero-waste' vision.